Limited Risk-Sharing and Capital Structure - Ulrich Schüwer (Verein für Socialpolitik, 2010)
This paper develops a model where firms' equilibrium capital structures depend on firms' risk characteristics and investors' aggregate risk appetite. I assume that the law of one price fails because security markets are incomplete and risk-sharing through short-selling or borrowing is limited. Investors have heterogeneous risk preferences. Thus, firms can create value through the issuance of debt and equity securities that optimally meet investor demand. I show that, in equilibrium, firms with high market risk have a lower debt ratio than firms with low market risk. Empirical evidence that completes this paper supports the relevance of this theoretical result.
Keywords: G32; D52; G12; 330; capital structure; security design; risk-sharing; segmented markets